The role of future land-use change in Southern Amazonia to reach the aims of Brazil’s National Climate Plan - Schaldach, Rüdiger; Göpel, Jan; Klingler, Michael (ERDKUNDE, 2017)
During the 1990s and early 2000s, forestry and agriculture were the main emitters of greenhouse gases in Brazil, contributing to approximately 80  % of the total national CO2-equivalent emissions. In Southern Amazonia, the conversion of forest and Cerrado ecosystems to pasture and cropland particularly resulted in high CO2-emissions from soils and vegetation. Other emissions from the agricultural sector include N2O emissions from the application of fertilisers and CH4 emissions from livestock. Only recently was significant progress made in decoupling further increases of agricultural production from deforestation rates. Given the expected increase in global demand for food, bioenergy and biomaterials in the coming years, it is uncertain whether the established policies and available technological potentials to improve crop productivity are sufficient to prevent further expansion of agricultural area. This would be an essential prerequisite for slowing down deforestation considerably and for achieving the national climate targets of reducing the annual greenhouse gas emission by 43 % in 2030. In order to explore the future pathways of land-use change in Southern Amazonia until 2030, we developed a set of four scenarios consisting of storylines and simulated high-resolution land-use maps. The scenarios take into consideration changing agricultural production due to changing commodity demands from domestic and global markets, as well as different assumptions regarding agricultural intensification and the effectiveness of policies targeting the preservation of protected areas. Based on the generated maps, greenhouse gas emissions (N2O, CH4 and CO2) were calculated. Emission reductions compared to the reference year 2010 could be achieved under the Legal Intensification (-38 %) and Sustainable Development (-79 %) scenarios. In both cases, the results indicate that further agricultural intensification together with strict conservation policies are essential requirements to slow down the loss of natural ecosystems and at the same time to reduce greenhouse gas emissions. Additionally, under Sustainable Development, a changing consumption pattern towards a more sustainable diet was identified as a suitable way to further mitigate the climate change impacts of agriculture.